Urinary isolates with special reference to Urichrom II - Mokkapati, Anuradha; Yalamanchili, Madhavi (International Journal of Research in Medical Sciences, 2017)
Urinary tract infections (UTIs) are the second most common infections, only after respiratory tract infections. Conventionally, Blood agar (BA), Mac Conkey agar (MAC) and Cysteine Lactose Electrolyte Deficient (CLED) medium are used routinely for processing of urine samples. Several chromogenic media are now available which can be used to allow more specific and direct differentiation of bacterial colonies on the primary plate itself. The following study was conducted to evaluate the advantages of URICHROM II over the conventional media in supporting the growth for routine urinary isolates. The study was conducted over a one year period (January 2012 to December 2012) at Hyderabad. A total of 3094 urine samples were processed during the one year period. The urine samples were inoculated on to blood agar (BA), Mac Conkey agar (MAC) and URICHROM II. The inoculated plates were incubated at 37°C over night (16-20 hr) and examined the next day morning. Samples showing significant bacterial growth (>105CFU/ml) were further processed. A total of 3094 urine samples were processed over a one year period. Out of the 3094 urine samples processed, 945 samples were positive (30.54%) and 2149 samples (69.45%) were negative. Among the positive samples (945), Gram positive isolates were obtained from 201 samples (21.22%) and Gram negative isolates from 744 samples (78.82%). Escherichia coli was the predominant Gram negative isolate (51.11%) and Enterococcus feacalis was the predominant Gram positive isolate (14.81%). URICHROM II supported the growth of all routine urinary isolates on par with BA and MAC and can be recommended as a primary plating medium for recovery of uropathogens.